Molecular heterogeneity of CD30+ peripheral T-cell lymphoma with prognostic significance and therapeutic implications: a retrospective multi-centre studyResearch in context - Yu-Jia Huo; Shu Cheng; Hong-Mei Yi; Ting Niu; Lei Fan; Guo-Hui Cui; Fu-Ling Zhou; Xian-Min Song; Fei Li; Ou Bai; Xiao-Jing Yan; Jun Shi; et al. (EBioMedicine)
Summary: Background: Peripheral T-cell lymphoma (PTCL) represents a highly heterogeneous group of non-Hodgkin's lymphomas, often with aggressive biological behaviour. CD30 serves as a pivotal surface antigen in PTCL, however, its biological functions and therapeutic potential warrant further investigation. Methods: We analysed 415 de novo patients with PTCL including 314 in the training cohort and 101 in the validation cohort across 11 medical centres in China. Genomic and transcriptomic profiles were examined by DNA- and RNA-sequencing in 355 and 169 patients, respectively. Findings: In both cohorts, CD30+ PTCL presented significantly increased frequencies of SETD2, STAT3, and PTPRS mutations. Therefore, three molecular subtypes with distinct biological signatures were identified, including the HMA subtype characterised by dysregulation of histone methylation and acetylation, the JNE subtype by alterations in JAK-STAT, Notch signalling pathway, and EBV infection, and the PCT subtype by mutations in phosphorylation, chromatin remodelling, and T-cell receptor-major histocompatibility complex interaction, with extracellular matrix enrichment. Clinically, the JNE subtype demonstrated inferior progression-free survival (PFS) and overall survival (OS), as compared to the HMA and PCT subtypes. Brentuximab vedotin (BV)-containing treatment was associated with improved PFS and OS in the JNE and PCT subtypes. Furthermore, gene expression profile analysis demonstrated underlying vulnerabilities for the HMA, JNE, and PCT subtypes to epigenome-targeting agents, JAK or PI3K inhibitors, and PD-1 inhibitors, respectively. Interpretation: The molecular subtypes of CD30+ PTCL demonstrated prognostic significance and varied sensitivity to BV treatment. Our findings further elucidated molecular regulatory networks of CD30+ PTCL, providing potential co-targeted approaches for genotype-guided precision medicine in PTCL. Funding: This study was supported by National Key R&D Program of China, National Natural Science Foundation of China, Clinical Research Plan of Shanghai Hospital Development Centre, Shanghai Clinical Research Centre for Cell Therapy, Shanghai Municipal Health Commission, and China Postdoctoral Science Foundation.